Morphology and Fertility of Soils of Southern Rajasthan (Udaipur Division) - Lodha, B. K.; Sanghi, C. L.; Jain, S. V. (Indian Forester, 1975)
17945 soil samples have been received from Southern Rajasthan. The analysis data is re-arranged according to soil groups found in the area. Brown soils of saline phase have lowest available nutrient content whereas deep medium black soils are highest in available nutrients, the other soils fall in between. Brown soils of saline phase have mare problems of salinity and alkalinity whereas red loam least. Fertiliser recommendations according to different soil groups are also discussed.